2014
DOI: 10.1038/srep07240
|View full text |Cite
|
Sign up to set email alerts
|

Probing Defects in Nitrogen-Doped Cu2O

Abstract: Nitrogen doping is a promising method of engineering the electronic structure of a metal oxide to modify its optical and electrical properties; however, the doping effect strongly depends on the types of defects introduced. Herein, we report a comparative study of nitrogen-doping-induced defects in Cu2O. Even in the lightly doped samples, a considerable number of nitrogen interstitials (Ni) formed, accompanied by nitrogen substitutions (NO) and oxygen vacancies (VO). In the course of high-temperature annealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 37 publications
11
60
0
Order By: Relevance
“…Further, the signature of the O 1s peak at 530.4 eV (see Fig. 3(B)) is consistent with O-state in Cu 2 O too [50]. .…”
Section: Characterization Of Cu 2 Osupporting
confidence: 77%
“…Further, the signature of the O 1s peak at 530.4 eV (see Fig. 3(B)) is consistent with O-state in Cu 2 O too [50]. .…”
Section: Characterization Of Cu 2 Osupporting
confidence: 77%
“…3(C) showed that the major contribution was due to the lattice oxygen atoms that are bound to the cerium ions positioned at~529.5 eV [40]. The peak appeared at 530.4 eV may have originated from the oxygen bind with the Cu 2 O [41]. The peaks located to the higher BE at 531.5 and 532.6 eV were attributed to the NiO and defect oxygen, respectively [42].…”
Section: Resultsmentioning
confidence: 91%
“…We also tried onestep method by spin-coating the mixed solution of PbCl 2 and CH 3 NH 3 I onto ITO/Cu 2 O, but no pure perovskite phase was achieved after annealing at 100 °C, which might be related to the surface properties of Cu 2 O films. [38][39][40] Further optimization of device performance was thus focused on using the two-step method since the residual PbI 2 provides the beneficial effect of passivation.…”
Section: Resultsmentioning
confidence: 99%